2015
DOI: 10.2298/vsp140209036l
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of Serbian version of children's dental fear questionnaire

Abstract: The Serbian version of CFSS-DS questionnaire is reliable and valid psychometric instrument for evaluation of dental fear in Serbian children. Dental anxiety negatively affects dental attendance and oral health of the examined schoolchildren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
3
6
0
5
Order By: Relevance
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 92%
See 1 more Smart Citation
“…The present study showed that mean anxiety score is significantly higher in girls than in boys (p=0.006). Our findings are similar to the findings of Ten Berge M et al (17), Maja L et al (18), Majstorovic et al (19), and Nakai et al (20). Some study had shown no significant difference in mean anxiety score between boys and girls (girl vs. boys mean CFSS-DS was 27.50+/-5.01, and 26.84+/-5.62, respectively) (21).…”
Section: Raspravasupporting
confidence: 92%
“…The highest Cronbach alpha score were calculated for S-DAI (0.991), CFSS-DS (0.974), PDAS (0.968), and OAS (0.961). The mean CFSS-DS score for the patients with dental trauma in the present study (20.44+/-8.50) were in concordance with previous study, but was lower than the finding in Netherland (23.2) (17), Serbia (26.47) (18), and Croatia (23.4 for male and 29.9 for female) (19). In our study the mean score CFSS-DS for male was 19.23+/-6.30 and for female 22.17+/-10.72.…”
Section: Raspravasupporting
confidence: 92%
“…The CFSS‐DS was developed to assess dental fear in children through a questionnaire consisting of a fifteen items . This scale is commonly used to measure dental fear, and it has been widely translated and validated in other countries . Thus, this study translated and validated the Brazilian version of the Dental Subscale of Children's Fear Survey Schedule (B‐CFSS‐DS).…”
Section: Discussionmentioning
confidence: 99%
“…The CFSS‐DS has been translated into many languages, such as Japanese, Greek, Hindi, Chinese, Arabic, Bosnian and Herzegovina, Serbian, and Italian, demonstrating good test‐retest reliability and good internal consistency. A survey tool having high reliability in some part of the world may not have universal validity unless its constituents are unaffected by cultural changes …”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, es el caso de sentir un pinchazo en la encía (Vika et al, 2008) o sentirse inquieto por los sonidos u olores del consultorio. Lalic et al (2015), en niños serbios de 12 años, evidenciaron que el mayor temor en la consulta odontológica es el tratamiento con la pieza de alta velocidad (perforación), por ejemplo. Estas situaciones pueden coincidir con la teoría de Iván Pavlov (1927), sobre condicionamiento clási-co, según la cual un individuo forma una asociación entre dos eventos.…”
Section: Discussionunclassified